Evaluating route preview as an alternative to turn-by-turn navigation in pedestrian mobility - Gian-Luca Savino; Emanuel de Bellis; Reuben Kirkham; Johannes Schöning (PLoS ONE, 2026)
Mobile navigation apps like Google Maps and Apple Maps predominantly use turn-by-turn (TBT) instructions for pedestrians, a paradigm originally designed for vehicular navigation. However, many users actively choose the simpler route preview (RP) mode, which displays only the mapped route without real-time guidance features. This research employs a three-study mixed-methods approach to investigate whether RP could serve as an effective alternative to TBT for pedestrian navigation. Study 1 surveyed user preferences (n = 222), revealing that 44% prefer RP despite its limited features, rising to 76% in familiar environments. Study 2 compared actual navigation performance (n = 195), finding no significant differences between modes across key metrics: navigation errors, phone glances, and spatial learning, with RP on par and even better for some key metrics. Study 3 was a co-design workshop (n = 5) to identify priority enhancements, including landmark integration, intention-based routing, and subtle orientation aids. Overall, these findings challenge the assumption that TBT represents optimal pedestrian navigation design. Instead, they demonstrate that RP, with its cognitive engagement benefits and user autonomy, performs comparably to TBT despite fewer features. When enhanced with targeted improvements, RP could better serve diverse pedestrian needs than current TBT-dominant interfaces. This work provides evidence-based guidance for developing more versatile, cognitively engaging pedestrian navigation systems.